Tunnel wall nano-silicon negative ion paint and preparation method thereof
Patent Information
- Application Number
- CN202611256137.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-19
AI Technical Summary
[0006]本发明的目的在于提供一种隧道壁纳米硅负离子涂料及其制备方法,以解决现有技术中负离子型隧道壁面装饰涂料的安全照明效果一般,长期使用过程中容易被油性污染物物理覆盖,失去长效稳定性的技术问题
1、本发明的隧道壁纳米硅负离子涂料包括A组分和B组分,A组分中的功能化α-磷酸锆纳米片会形成平行于基材表面的层状有序结构,可以增强涂层的安全照明效果,将隧道灯具发出的光线高效、均匀地反射至路面,提升路面亮度均匀度。并且其表面含有可聚合碳碳双键,能够在固化过程中与含氟不饱和单体以及交联剂之间发生共聚,形成包裹在纳米片上的疏油分子,从而使汽车尾气中的油性碳烟和粉尘无法铺展和粘附,从根源上杜绝了物理覆盖层的形成,提高负离子释放的长期稳定。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coatings technology, and in particular to a tunnel wall nano-silicon negative ion coating and its preparation method. Background Technology
[0002] As a crucial component of highway transportation, tunnels are characterized by their enclosed, narrow interiors and limited ventilation. The tunnel walls serve as primary visual reference surfaces for drivers, and the performance of their decorative coatings directly impacts driving safety and comfort. In addition to enhanced lighting at tunnel entrances and exits, full-section coating can effectively improve tunnel illumination, reduce visual discomfort, and enhance driving safety and comfort. Existing tunnel wall decorative coatings, by increasing the light reflectivity of the coating, can effectively increase tunnel brightness through repeated light reflection from the tunnel walls without requiring additional lighting fixtures. Furthermore, tunnel wall decorative coatings can alleviate drivers' psychological stress and beautify the environment by creating a bright and clean visual space.
[0003] Existing tunnel wall decorative coatings mainly use synthetic resins as film-forming substances, while negative ion coatings add negative ion powder to the coating formula so that the coating continuously ionizes air molecules under photocatalysis, releasing a large number of negative oxygen ions. On the one hand, it can purify the air, as negative ions can actively capture and neutralize positively charged harmful substances in exhaust gas, causing them to settle and decompose; on the other hand, it can further improve the lighting environment.
[0004] However, with existing negative ion coatings, oily particles and dust from vehicle exhaust physically coat the coating surface. Since highway tunnels are primarily filled with oily pollutants, and oil has a much higher surface tension than water, the surface energy requirements for oleophobic coatings are more stringent. The physical coating layer formed by oily pollutants severely obscures the photocatalytic active sites of the negative ion powder, hindering light penetration to the photocatalytic material surface. This significantly inhibits the photocatalytic generation of negative ions, leading to a substantial decrease in negative ion release and the loss of self-cleaning effect.
[0005] Therefore, it is of great significance to develop a novel nano-silicon negative ion coating for tunnel walls that can continuously release negative ions to purify tunnel air, effectively resist the physical coverage of oily pollutants, maintain long-term stability of photocatalytic activity, and improve safe lighting and spatial environment. Summary of the Invention
[0006] The purpose of this invention is to provide a nano-silicon negative ion coating for tunnel walls and its preparation method, so as to solve the technical problems of the existing negative ion tunnel wall decorative coatings having mediocre safety lighting effects and being easily covered by oily contaminants during long-term use, thus losing long-term stability.
[0007] The technical problem to be solved by this invention can be achieved through the following technical solution: In a first aspect, the present invention provides a tunnel wall nano-silicon negative ion coating, comprising component A and component B; component A comprises the following raw materials in parts by weight: 40–55 parts of nano-silicate aqueous solution; 6–12 parts of functionalized zirconium α-phosphate nanosheets; Initiator 0.2–0.5 parts; 10-20 parts deionized water; Component B comprises the following raw materials in parts by weight: 20-30 parts of nano-silica sol; Visible light responsive tourmaline / nano titanium dioxide composite negative ion powder, 8-15 parts; 3-8 parts of fluorinated unsaturated monomers; Crosslinking agent 0.5-1 part; Other additives: 0.5–2 parts; 15-25 parts deionized water; The surface of functionalized α-zirconium phosphate nanosheets contains double bonds.
[0008] Preferably, the fluorinated unsaturated monomers include one or more combinations of dodecafluoroheptyl methacrylate, hexafluorobutyl methacrylate, perfluorooctyl ethyl acrylate, perfluorooctyl ethyl methacrylate, pentafluorostyrene, and p-fluorostyrene.
[0009] Preferably, the nano-silicate aqueous solution includes any one of sodium silicate aqueous solution, potassium silicate aqueous solution, and lithium cobalt oxide aqueous solution with a solid content of 25-35%.
[0010] Preferably, the crosslinking agent includes one or more combinations of divinylbenzene, ethylene glycol dimethacrylate, triethylene glycol diacrylate, and trimethylolpropane triacrylate.
[0011] Preferably, the nano-silica sol undergoes a pretreatment process modified with an aminosilane coupling agent, including the following steps: The nano-silica sol is diluted with isopropanol, then an aminosilane coupling agent is added, and the mixture is stirred at room temperature for 2–4 hours to obtain the final product.
[0012] Preferably, the mass ratio of component A to component B is 1:(1 to 1.5).
[0013] More preferably, the initiator includes one or more combinations of potassium persulfate, ammonium persulfate, hydrogen peroxide, sodium bisulfite, and sodium thiosulfate.
[0014] More preferably, other additives include leveling agents and defoamers.
[0015] By adopting the above technical solution, the tunnel wall nano-silicon negative ion coating of the present invention includes component A and component B. After component A and component B are mixed and cured, a coating can be formed through in-situ polymerization and self-assembly. The functionalized α-zirconium phosphate nanosheets in component A form a layered ordered structure parallel to the substrate surface, exhibiting extremely high diffuse reflectance of visible light. This layered reflective structure can enhance the safety lighting effect of the coating, efficiently and uniformly reflecting the light emitted by tunnel lights to the road surface, improving the uniformity of road surface brightness, and eliminating the oppressive "black hole effect." Moreover, it can directly reduce the power or number of tunnel lighting fixtures, achieving significant energy savings in lighting.
[0016] Furthermore, the functionalized α-zirconium phosphate nanosheets of the present invention contain polymerizable carbon-carbon double bonds on their surface, which can copolymerize with fluorinated unsaturated monomers and crosslinking agents during the curing process. Moreover, since the double bonds are covalently grafted onto the surface of the α-zirconium phosphate nanosheets, the polymerization reaction can be precisely confined around the nanosheets. The fluorinated unsaturated monomers form oleophobic molecules wrapped around the nanosheets, thereby preventing oily soot and dust in automobile exhaust from spreading and adhering, thus eliminating the formation of a physical coating layer at the source.
[0017] Simultaneously, air molecules can freely enter and exit the visible light-responsive tourmaline / nano titanium dioxide composite negative ion powder inside. Tourmaline has a natural spontaneous polarization effect, which can ionize the air to generate negative ions under weak environmental energy; the loading of nano titanium dioxide endows it with photocatalytic function. By efficiently stimulating air negative ions, the coating maintains a stable negative ion release rate even under heavy pollution conditions in tunnels.
[0018] The nano-silica negative ion coating for tunnel walls of the present invention uses a nano-silicate system as the main film-forming system. The nano-silicate aqueous solution can provide basic adhesion and has excellent adhesion to tunnel concrete substrate. The nano-silica sol is also treated with a silane coupling agent, which can further help the nano-silica sol to undergo silanol condensation with the nano-silicate during the curing process to form a continuous Si-O-Si inorganic network.
[0019] However, although traditional silicate coatings have good adhesion to tunnel walls, nano-silicates have poor water resistance and low hydrolytic stability, which directly affects long-term performance and curing processability. The traditional method to improve the water resistance of silicate coatings is mainly to increase the density of the coating, but this will block the channels for water vapor and air to contact the internal negative ion powder, affecting the release of negative ions.
[0020] The functionalized α-zirconium phosphate nanosheets in this invention, after curing with fluorine-containing unsaturated monomers, undergo microscopic volume shrinkage within the resulting coating. Subsequently, under the influence of steric hindrance and anisotropic stress, the high aspect ratio nanosheets are forced to align parallel to the substrate, significantly increasing the tortuosity of the water molecule penetration path and fundamentally solving the problem of poor water resistance in inorganic silicate networks. Therefore, the resulting coating combines water resistance with negative ion release characteristics.
[0021] Preferably, the raw materials for functionalized α-zirconium phosphate nanosheets include α-zirconium phosphate nanosheets, tetrabutylammonium hydroxide and vinylsilane coupling agent in a mass ratio of 10:(2-4):(0.2-0.3).
[0022] Preferably, functionalized α-zirconium phosphate nanosheets are prepared according to the following method: After dispersing α-zirconium phosphate nanosheets in water, a 10-15% (w / w) tetrabutylammonium hydroxide solution was added and stirred for 30-60 min. Then, the mixture was centrifuged, washed, and dried to obtain pretreated α-zirconium phosphate nanosheets. Pretreated zirconium phosphate nanosheets were dispersed in ethanol, and a vinylsilane coupling agent was added. The mixture was stirred at 60–65 °C for 1–2 h, then allowed to stand and filtered. After washing and drying, functionalized zirconium phosphate nanosheets were obtained.
[0023] By adopting the above technical solution, the functionalized α-zirconium phosphate nanosheets of the present invention are first subjected to intercalation modification treatment, so that the cations ionized from tetrabutylammonium hydroxide in water can enter the interlayer, increase the interlayer spacing of the α-zirconium phosphate nanosheets, and expose more active sites. Then, they are grafted with vinylsilane coupling agent to graft carbon-carbon double bonds that can participate in free radical polymerization onto the surface of the α-zirconium phosphate nanosheets.
[0024] During the curing process, the functionalized α-zirconium phosphate nanosheets undergo large-scale, long-range ordered orientation along a direction parallel to the tunnel wall, making the water molecule penetration path extremely tortuous and fundamentally solving the water resistance bottleneck of inorganic silicate networks. Furthermore, the surface double bonds undergo in-situ copolymerization with the fluorinated unsaturated monomers and crosslinking agents in component B under the action of an initiator, resulting in extremely low surface energy of the nanosheet layer. This strongly repels exhaust gas and oil stains, thus ensuring long-term stable negative ion release.
[0025] Preferably, component B also includes 1 to 3 parts by mass of graphitic carbon nitride.
[0026] By adopting the above technical solution, graphitic carbon nitride is also introduced into component B of the present invention. On the one hand, when the graphitic carbon nitride nanosheets are mixed, they will spontaneously wrap around the visible light responsive tourmaline / nano titanium dioxide composite negative ion powder particles, which can form a physical barrier between them and the oleophobic layer formed after the functionalized α-zirconium phosphate nanosheets are polymerized, preventing the photocatalytic degradation of oleophobic molecules by titanium dioxide and extending the effective period of key oleophobic functions.
[0027] On the other hand, graphitic carbon nitride and titanium dioxide have matching band structures, and their composite structure forms a Z-shaped heterojunction. Under visible light irradiation, the high recombination rate of electron-hole pairs within a single titanium dioxide catalyst is greatly suppressed, resulting in a multiple increase in catalytic efficiency, thereby improving self-cleaning ability and further amplifying the generation of negative ions under light irradiation.
[0028] Secondly, the present invention provides a method for preparing a tunnel wall nano-silicon negative ion coating, which includes the following process steps: S1. Functionalized α-zirconium phosphate nanosheets were added to deionized water and stirred to disperse them. Then, they were mixed and dispersed with an aqueous solution of nano-silicates. An initiator was added, and the mixture was stirred to obtain component A. S2. Fluorine-containing unsaturated monomers and crosslinking agents are added to nano-silica sol and stirred to disperse to obtain a premix. Other raw materials are added to deionized water and then stirred and mixed evenly with the premix to obtain component B. S3. Mix component A and component B according to the mass ratio to obtain the tunnel wall nano-silicon negative ion coating.
[0029] The beneficial effects of this invention are: 1. The tunnel wall nano-silicon negative ion coating of the present invention comprises component A and component B. The functionalized α-zirconium phosphate nanosheets in component A form a layered ordered structure parallel to the substrate surface, which can enhance the safety lighting effect of the coating, efficiently and uniformly reflect the light emitted by the tunnel lights to the road surface, and improve the uniformity of road surface brightness. Furthermore, its surface contains polymerizable carbon-carbon double bonds, which can copolymerize with fluorine-containing unsaturated monomers and crosslinking agents during the curing process to form oleophobic molecules encapsulated on the nanosheets. This prevents oily soot and dust from automobile exhaust from spreading and adhering, fundamentally eliminating the formation of a physical coating layer and improving the long-term stability of negative ion release.
[0030] 2. The tunnel wall nano-silicon negative ion coating of this invention adopts a silicate system. The aqueous solution of nano-silicates provides basic adhesion and cross-links and condenses with nano-silica sol to form a continuous Si-O-Si inorganic network. Furthermore, the oriented arrangement structure formed by functionalized α-zirconium phosphate nanosheets greatly increases the tortuosity of the water molecule penetration path, fundamentally solving the problem of poor water resistance of inorganic silicate networks and improving overall stability. Detailed Implementation
[0031] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0032] Preparation Example Preparation Example 1-1: A functionalized α-zirconium phosphate nanosheet was prepared according to the following method: 10g of α-zirconium phosphate nanosheets (average particle size of 500nm) were dispersed in water and then added to 30mL of 10% tetrabutylammonium hydroxide solution. The mixture was stirred for 60min and then centrifuged, washed and dried to obtain pretreated α-zirconium phosphate nanosheets. Pretreated zirconium phosphate nanosheets were dispersed in ethanol, and 0.25 g of γ-methacryloyloxypropyltrimethoxysilane was added. The mixture was stirred at 60 °C for 2 h, then allowed to stand and filtered. After washing and drying, functionalized zirconium phosphate nanosheets were obtained.
[0033] Preparation Examples 1-2: A functionalized α-zirconium phosphate nanosheet was prepared according to the following method: 10g of α-zirconium phosphate nanosheets (average particle size of 500nm) were dispersed in water and then added to 20mL of 10% tetrabutylammonium hydroxide solution. The mixture was stirred for 60min and then centrifuged, washed and dried to obtain pretreated α-zirconium phosphate nanosheets. Pretreated zirconium phosphate nanosheets were dispersed in ethanol, and 0.3 g of γ-methacryloyloxypropyltrimethoxysilane was added. The mixture was stirred at 60 °C for 2 h, then allowed to stand and filtered. After washing and drying, functionalized zirconium phosphate nanosheets were obtained.
[0034] Preparation Examples 1-3: A functionalized α-zirconium phosphate nanosheet was prepared according to the following method: 10g of α-zirconium phosphate nanosheets (average particle size of 500nm) were dispersed in water and then added to 40mL of 10% tetrabutylammonium hydroxide solution. The mixture was stirred for 60min and then centrifuged, washed and dried to obtain pretreated α-zirconium phosphate nanosheets. Pretreated zirconium phosphate nanosheets were dispersed in ethanol, and 0.2 g of γ-methacryloyloxypropyltrimethoxysilane was added. The mixture was stirred at 60 °C for 2 h, then allowed to stand and filtered. After washing and drying, functionalized zirconium phosphate nanosheets were obtained.
[0035] Preparation Examples 1-4: A functionalized α-zirconium phosphate nanosheet was prepared according to the following method: 10g of α-zirconium phosphate nanosheets were dispersed in ethanol, and 0.25g of γ-methacryloyloxypropyltrimethoxysilane was added. The mixture was stirred at 60℃ for 2h, then allowed to stand and filtered. After washing and drying, functionalized α-zirconium phosphate nanosheets were obtained.
[0036] Preparation Example 2-1: A nano-silica sol was modified and pretreated according to the following method: 100g of nano silica sol (particle size 10-25nm, solid content 30%) was diluted with 15mL of isopropanol, and then 15g of γ-glycidoxypropyltrimethoxysilane was added. The mixture was stirred at room temperature for 3h to obtain the final product.
[0037] Example Example 1: A nano-silicon negative ion coating for tunnel walls was prepared according to the following method: S1. Add 9 parts of the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1 to 15 parts of deionized water and stir to disperse. Then mix and disperse with 50 parts of sodium silicate nano-aqueous solution. Add 0.4 parts of ammonium persulfate and stir to obtain component A. S2. Add 5 parts of dodecafluoroheptyl methacrylate and 0.8 parts of divinylbenzene to 25 parts of the nano silica sol prepared in Preparation Example 2-1, stir and disperse to obtain a premixed solution, add 12 parts of visible light responsive tourmaline / nano titanium dioxide composite negative ion powder and 1 part of leveling agent BYK-330 to 20 parts of deionized water, and then stir and mix evenly with the premixed solution to obtain component B.
[0038] The tunnel wall nano-silicon negative ion coating is obtained by mixing components A and B at a mass ratio of 1:1.2.
[0039] Example 2: A nano-silicon negative ion coating for tunnel walls, prepared according to the following method: S1. Add 6 parts of the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1 to 20 parts of deionized water and stir to disperse. Then mix and disperse with 40 parts of sodium silicate nano-aqueous solution. Add 0.2 parts of ammonium persulfate and stir to obtain component A. S2. Add 3 parts dodecafluoroheptyl methacrylate and 0.5 parts divinylbenzene to 30 parts of the nano silica sol prepared in Preparation Example 2-1, stir and disperse to obtain a premixed solution, add 15 parts visible light responsive tourmaline / nano titanium dioxide composite negative ion powder and 1 part leveling agent BYK-330 to 15 parts of deionized water, and then stir and mix with the premixed solution to obtain component B.
[0040] The tunnel wall nano-silicon negative ion coating is obtained by mixing components A and B at a mass ratio of 1:1.2.
[0041] Example 3: A nano-silicon negative ion coating for tunnel walls, prepared according to the following method: S1. Add 12 parts of the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1 to 10 parts of deionized water and stir to disperse. Then mix and disperse with 55 parts of sodium nanosilicate aqueous solution. Add 0.5 parts of ammonium persulfate and stir to obtain component A. S2. Add 8 parts of dodecafluoroheptyl methacrylate and 1 part of divinylbenzene to 20 parts of the nano silica sol prepared in Preparation Example 2-1, stir and disperse to obtain a premixed solution, add 8 parts of visible light responsive tourmaline / nano titanium dioxide composite negative ion powder and 1 part of leveling agent BYK-330 to 25 parts of deionized water, and then stir and mix with the premixed solution to obtain component B.
[0042] The tunnel wall nano-silicon negative ion coating is obtained by mixing components A and B at a mass ratio of 1:1.2.
[0043] Example 4: A tunnel wall nano-silicon negative ion coating, which differs from Example 1 only in that the functionalized α-zirconium phosphate nanosheets prepared in Example 1-1 are replaced with an equal amount of functionalized α-zirconium phosphate nanosheets prepared in Example 1-2.
[0044] Example 5: A tunnel wall nano-silicon negative ion coating, which differs from Example 1 only in that the functionalized α-zirconium phosphate nanosheets prepared in Example 1-1 are replaced with an equal amount of functionalized α-zirconium phosphate nanosheets prepared in Example 1-3.
[0045] Example 6: A tunnel wall nano-silicon negative ion coating, the only difference from Example 1 is that an equal amount of nano-potassium silicate aqueous solution is used instead of nano-sodium silicate aqueous solution.
[0046] Example 7: A tunnel wall nano-silicon negative ion coating was prepared according to the following method: S1. Add 9 parts of the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1 to 15 parts of deionized water and stir to disperse. Then mix and disperse with 50 parts of sodium silicate nano-aqueous solution. Add 0.4 parts of ammonium persulfate and stir to obtain component A. S2. Add 5 parts of dodecafluoroheptyl methacrylate and 0.8 parts of divinylbenzene to 25 parts of the nano silica sol prepared in Preparation Example 2-1, stir and disperse to obtain a premixed solution. Add 12 parts of visible light responsive tourmaline / nano titanium dioxide composite negative ion powder, 2 parts of graphitic carbon nitride, and 1 part of leveling agent BYK-330 to 20 parts of deionized water, and then stir and mix with the premixed solution to obtain component B.
[0047] The tunnel wall nano-silicon negative ion coating is obtained by mixing components A and B at a mass ratio of 1:1.2.
[0048] Example 8, a tunnel wall nano-silica negative ion coating, differs from Example 1 only in that an equal amount of untreated nano-silica sol is used to replace the nano-silica sol prepared in Preparation Example 2-1.
[0049] Example 9, a tunnel wall nano-silicon negative ion coating, differs from Example 1 only in that the functionalized α-zirconium phosphate nanosheets prepared in Example 1-1 are replaced with an equal amount of functionalized α-zirconium phosphate nanosheets prepared in Example 1-4.
[0050] Comparative Example Comparative Example 1 is a tunnel wall nano-silicon negative ion coating, which differs from Example 1 only in that an equal amount of unmodified α-zirconium phosphate nanosheets are used to replace the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1.
[0051] Comparative Example 2, a tunnel wall nano-silicon negative ion coating, differs from Example 1 only in that dodecafluoroheptyl methacrylate is not added during the preparation of component B.
[0052] Comparative Example 3, a tunnel wall nano-silicon negative ion coating, differs from Example 1 only in that the amount of functionalized α-zirconium phosphate nanosheets prepared in Example 1-1 added is 15 parts.
[0053] Comparative Example 4, a tunnel wall nano-silicon negative ion coating, differs from Example 1 only in that the functionalized α-zirconium phosphate nanosheets prepared in Preparation Example 1-1 are not added to component A.
[0054] Performance testing Using a tunnel simulation chamber, the nano-silicon negative ion coating for the tunnel wall obtained in the examples and comparative examples was coated on a 300mm×200mm×5mm concrete slab substrate. The coating was then applied in a sealed test chamber (0.1m³). 3 In the center, use an air ion meter to test the initial negative ion release, and then: (1) In the tunnel environment simulation chamber (temperature 25℃, relative humidity 85%, ventilation airflow 0.5m / s, periodically introduce mixed gas containing trace amounts of NO2 and CO2 to simulate tunnel air, and turn on LED lights for 12 hours a day), run continuously for 30 days, and test the negative ion release again.
[0055] (2) In a closed fume exposure box, commercial diesel fuel is burned inside the box to produce continuous fumes (the concentration of oily carbon soot particles is approximately 200 mg / m³). 3 The temperature was maintained at 35℃ for 24 hours, and the negative ion release was tested again to calculate the negative ion release retention rate.
[0056] Immerse the cured sample in a deionized water bath at a constant temperature of 40°C, ensuring the water level is always at least 5 cm above the top edge of the sample, and observe continuously. Record the observation results.
[0057] The results of the above experiments are shown in Table 1: Table 1 Performance test results
[0058] According to Table 1, combined with Examples 1 and 9, it can be seen that the performance of each item has decreased compared with Example 1. The reason may be that the functionalized α-zirconium phosphate nanosheets have not undergone intercalation pretreatment, the nanosheets are severely stacked, and they cannot be effectively oriented and assembled, resulting in limited water molecule impermeability and reduced oleophobic effect.
[0059] Combining Example 1 with Comparative Examples 1, 3, and 4, it can be seen that the performance of Comparative Examples 1, 3, and 4 is lower than that of Example 1. This may be because the α-zirconium phosphate nanosheets in Comparative Example 1 were not functionalized, thus failing to form an ordered layered structure and oleophobic microdomains. Relying solely on physical filling, they exhibit poor water resistance and lack oil stain resistance, resulting in rapid decay of negative ions. Comparative Example 3, on the other hand, added excessive amounts of functionalized α-zirconium phosphate nanosheets, leading to insufficient interlayer bonding, coating embrittlement, and microcracks. Water molecules rapidly penetrated the coating, and the excessive encapsulation of negative ion powder hindered its release, resulting in decreased performance. Comparative Example 4, lacking functionalized α-zirconium phosphate nanosheets, lacked a layered structure, directly exposing the inorganic network, significantly reducing water resistance. The homopolymerization of fluorinated unsaturated monomers formed isolated hydrophobic microdomains without spatial confinement, failing to effectively protect the negative ion powder and exhibiting weak oil stain resistance.
[0060] Combining Example 1 and Comparative Example 2, it can be seen that the performance of Comparative Example 2 is lower than that of Example 1. The reason may be that no fluorine-containing unsaturated monomer was added in Comparative Example 2, and the oil directly covered the surface of the negative ion powder, causing it to lose its function and suffer severe attenuation.
[0061] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A nano-silicon negative ion coating for tunnel walls, characterized in that, It includes component A and component B; component A comprises the following raw materials in parts by weight: 40–55 parts of nano-silicate aqueous solution; 6–12 parts of functionalized zirconium α-phosphate nanosheets; Initiator 0.2–0.5 parts; 10-20 parts deionized water; Component B comprises the following raw materials in parts by weight: 20-30 parts of nano-silica sol; Visible light responsive tourmaline / nano titanium dioxide composite negative ion powder, 8-15 parts; 3-8 parts of fluorinated unsaturated monomers; Crosslinking agent 0.5-1 part; Other additives: 0.5–2 parts; 15-25 parts deionized water; The functionalized zirconium phosphate nanosheets contain double bonds on their surface; The functionalized α-zirconium phosphate nanosheets were prepared according to the following method: After dispersing α-zirconium phosphate nanosheets in water, a 10-15% (w / w) tetrabutylammonium hydroxide solution was added and stirred for 30-60 min. Then, the mixture was centrifuged, washed, and dried to obtain pretreated α-zirconium phosphate nanosheets. Pretreated zirconium phosphate nanosheets were dispersed in ethanol, and a vinylsilane coupling agent was added. The mixture was stirred at 60–65 °C for 1–2 h, then allowed to stand and filtered. After washing and drying, functionalized zirconium phosphate nanosheets were obtained.
2. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The raw materials for the functionalized α-zirconium phosphate nanosheets include α-zirconium phosphate nanosheets, tetrabutylammonium hydroxide and vinylsilane coupling agent in a mass ratio of 10:(2-4):(0.2-0.3).
3. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The fluorinated unsaturated monomers include one or more combinations of dodecafluoroheptyl methacrylate, hexafluorobutyl methacrylate, perfluorooctyl ethyl acrylate, perfluorooctyl ethyl methacrylate, pentafluorostyrene, and p-fluorostyrene.
4. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The nano-silicate aqueous solution includes any one of sodium silicate aqueous solution, potassium silicate aqueous solution, and lithium silicate aqueous solution; the solid content of the nano-silicate aqueous solution is 25-35%.
5. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The B component also includes 1 to 3 parts by mass of graphitic carbon nitride.
6. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The crosslinking agent includes one or more combinations of divinylbenzene, ethylene glycol dimethacrylate, triethylene glycol diacrylate, and trimethylolpropane triacrylate.
7. The tunnel wall nano-silicon negative ion coating according to claim 1, characterized in that, The mass ratio of component A to component B is 1:(1 to 1.5).
8. A method for preparing a tunnel wall nano-silicon negative ion coating, used to prepare the tunnel wall nano-silicon negative ion coating according to any one of claims 1 to 7, characterized in that, The process includes the following steps: S1. Functionalized α-zirconium phosphate nanosheets were added to deionized water and stirred to disperse them. Then, they were mixed and dispersed with an aqueous solution of nano-silicates. An initiator was added, and the mixture was stirred to obtain component A. S2. Fluorine-containing unsaturated monomers and crosslinking agents are added to nano-silica sol and stirred to disperse to obtain a premix. Other raw materials are added to deionized water and then stirred and mixed evenly with the premix to obtain component B.
Citation Information
Patent Citations
Negative oxygen ion light-emitting UHPC board and preparation method and equipment thereof
CN112851268A
Composition for coating the surface of architectureand producing method thereof
KR1020030069616A